Beat-to-beat blood pressure variability and heart rate variability in relation to autonomic dysregulation in patients with acute mild-moderate ischemic stroke. (June 2019) - Tian, Ge; Xiong, Li; Leung, Howan; Soo, Yannie; Leung, Thomas; Wong, Lawrence Ka-sing
Highlights: Autonomic dysregulation is underdiagnosed in this population due to a lack of simpler diagnostic tools. To correlate beat-to-beat BPV and HRV with Ewing's test classification. Autonomic dysregulation is associated with lower variation of blood pressure and heart rate in acute ischemic stroke. Non-invasive monitoring of beat-to-beat BPV and HRV may be an alternative to autonomic dysregulation measure. In clinic, we may use the cut-off values of LF/HF RRI, LF/HF dBP and LF/HF sBP for diagnosis of autonomic dysfunction. Abstract: Autonomic dysregulation is common in post-stroke patients. We aimed to correlate beat-to-beat blood pressure variability (BPV) and heart rate variability (HRV) with Ewing's test classification. We enrolled patients with acute ischemic stroke. Autonomic function was assessed by Ewing battery and dichotomized into minor or significant group. Beat-to-beat blood pressure and heart rate were monitored for calculating the frequency components of BPV and HRV using power spectral analysis [very low frequency (VLF; <0.04 Hz); low frequency (LF; 0.04–0.15 Hz); high frequency (HF; 0.15–0.40 Hz); power spectral density (PSD; <0.40 Hz) and LF/HF ratio]. In minor autonomic dysregulation group, BPV and HRV were similar with those in controls (all p > 0.05). However, LF/HF ratio in BPV and HRV significantly reduced in significant autonomic dysregulation group compared with that in controls (all p < 0.05). LF BPV in significant group was lower than that in controls. In patients, LF and LF/HF BPVs were positively correlated with parasympathetic parameters, while VLF HRV was negatively correlated with sympathetic parameters and the others were positively correlated with parasympathetic parameters. With cut-off values of 1.80 for LF/HF diastolic BP, 0.96 for the LF/HF systolic BP and 1.80 for LF/HF HRV, the sensitivity (53.80%, 69.20% and 53.80%, respectively) and specificity (92.50%, 80.00% and 92.50%, respectively) of these parameters were observed to predict autonomic dysregulation. Autonomic dysregulation is associated with lower variation of blood pressure and heart rate in acute ischemic stroke. Non-invasive monitoring of beat-to-beat BPV and HRV may be an alternative to autonomic dysregulation measure.